Plant breeding and cultivar development - Singh, Dhan Pal (Academic Press, 2021)
Plant Breeding and Cultivar Development features an optimal balance between classical and modern tools and techniques related to plant breeding. Written for a global audience and based on the extensive international experience of the authors, the book features pertinent examples from major and minor world crops. Advanced data analytics (machine learning), phenomics and artificial intelligence are explored in the book's 28 chapters that cover classical and modern plant breeding. By presenting these advancements in specific detail, private and public sector breeding programs will learn about new, effective and efficient implementation.The insights are clear enough that non-plant breeding majoring students will find it useful to learn about the subject, while advanced level students and researchers and practitioners will find practical examples that help them implement their work.